EXPLORING THE MAJOR FACTORS INFLUENCING OCCUPATIONAL STRESS AMONG CONSTRUCTION WORKERS (International Journal of Food and Nutritional Sciences, 2022)
Occupational stress among construction workers is a crucial concern in today’s fastpaced and demanding work environment. Construction sites are known to be challenging worksetting due to high risk nature of the job, physical demands, time pressure and constantlychanging conditions. The main of the study is to examine the important factors which influencedby occupational stressors that these the workers face and their impact on their mental andphysical well-being. It is important to understand the stressors that construction workersencounter on a daily basis. This stressor can stem from work related factors such as long workinghours, tight deadlines, job insecurity and frequent changes in work environment, poorinterpersonal relationship, excessive workload and lack of control over work related decision.Additionally, construction workers may also face stressors outside of work such as financialburdens, family issues and health concerns. It highlights the need for interventions and supportsystems to alleviate the stressors faced by construction workers. Both Primary and secondarydata were used for this study, 120 sample respondents were taken randomly for analysis purpose.Based on the findings, the researcher recommendations can be made for implementing measuressuch as training programs, improving safety standards, providing mental health support, andfostering better work-life balance to enhance overall well-being